Design of a Web-Based Book Dropshipping Information System - Doni Fransiscoly Simanjuntak; Emerson Porman Malau (Jurnal Info Sains : Informatika dan Sains, 2026)
The rapid development of information system technology has influenced the business world, including trade, so that the dropshipping system has become popular; however, William Bookstore still conducts direct transactions on site without stock recording, so customers have to come to the store and book availability information is inaccurate. To overcome this problem, this study designed a web-based Book Dropshipping Information System using the Waterfall method—including needs analysis, ERD and UML design, implementation with PHP and MySQL, and testing—so that customers can search and buy books without coming directly, and the store can monitor stock easily. As a result, the system built is able to facilitate purchase transactions, record stock, and purchase history automatically, provide real-time monitoring, increase order transparency, and become an effective solution in supporting shopping convenience and store record management.